2016
DOI: 10.1177/1359104516678039
|View full text |Cite
|
Sign up to set email alerts
|

Autism and reactive attachment/disinhibited social engagement disorders: Co-occurrence and differentiation

Abstract: DSM-5 ( Diagnostic and Statistical Manual of Mental Disorders, 5th edition) Reactive Attachment Disorder (RAD) and Disinhibited Social Engagement Disorder (DSED) are rare disorders sharing social difficulties with autism. The DSM-5 and ICD-10 (International Classification of Diseases, 10th revsion) state that RAD/DSED should not be diagnosed in children with autism. The purpose of our study is to determine whether children can meet criteria for both autism and RAD/DSED and to identify specific symptoms discrim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
49
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 31 publications
8
49
1
1
Order By: Relevance
“…Finding a high covariance between RAD and ASD is reflective of this. Nonetheless, the model differential test indicated that RAD and ASD are best conceptualized as different disorders, supporting previous findings that RAD and ASD are indeed differentiable [12,51].…”
Section: Discriminant Validitysupporting
confidence: 83%
“…Finding a high covariance between RAD and ASD is reflective of this. Nonetheless, the model differential test indicated that RAD and ASD are best conceptualized as different disorders, supporting previous findings that RAD and ASD are indeed differentiable [12,51].…”
Section: Discriminant Validitysupporting
confidence: 83%
“…Conversely, if a child is allowed physical play with his/ her parents and forms parent!child attachment, the child does not need to watch television. Children with no opportunity to develop an attachment relationship, as if like our patient, are at increased risk of a variety of social and behavioral problems, including an autistic-like pattern (9). Our patient's CARS score, which is a useful guide to the severity of ASD, improved after he was forbidden to watch videos.…”
Section: Discussionmentioning
confidence: 62%
“…RAD usually begins before the age of 5 years and persists over time (10-12). It results from a lack of basic emotional attachment and/or pathogenic care conditions, particularly during the first years of childhood (12,13). The disorder has also been strongly associated with early maltreatment and affects deprivation by the primary caregiver, typically through abuse, neglect, and abandonment (4,7,14).…”
Section: Introductionmentioning
confidence: 99%
“…Allen (15) mentions that RAD is currently considered essentially "the absence of a preferred attachment to anyone". A diagnostic requirement for this disorder is social neglect, which is the absence of adequate caregiving during childhood (13). In RAD children, psychological depression leads to increased levels of cortisol, inefficiencies in the functioning of serotonin and other neurotransmitters and reduced growth-hormone production (12,16).…”
Section: Introductionmentioning
confidence: 99%